Productividad de Pleurotus ostreatus em residuos de Amazônia - Sales-Campos, Ceci; De Almeida Minhoni, Marli Teixeira [UNESP]; De Andrade, Meire Cristina Nogueira (My University, 2010)
The viability of the utilization of wood and agroindustrial residues available in the Amazon region in the formulation of alternative substrates for the cultivation of Pleurotus ostreatus was tested. Thus, two wood residues: marupá sawdust (SIAMP) and pau-de-balsa sawdust (SAPB), and two substrates derived from agroindustrial residues: sugar-cane bagasse (SIACN) and pupunheira stem (SIAPP), were used. These were supplemented with a mixture of rice bran, wheat and corn as protein source, with addition of 2-3% of CaCO3 for pH correction (6.5). The substrates were placed in polyethylene (HDPE) bags, sterilized at 121°C for 1h and inoculated in a laminar flow chamber. The cultivation was carried out in an axenic way, in a modified atmosphere. The productivity of the substrates was evaluated in relation to the biological efficiency, with the following mean results: 125.60, 99.80%, 94.00 and 64.60% for SIAPP, SIACN, SIAMP and SIAPB, respectively. The high biological efficiency of the substrates and the cultivation process clearly showed the viability of the utilization of the residues, suggesting the commercial cultivation of this mushroom, which may contribute for improving the social and economical conditions and sustainability of the regional biodiversity resources of Amazonia.
Productivity of pleurotus ostreatus in Amazonian residues